Peningkatan Kompetensi Guru SMK Melalui Pelatihan Komputer Perpajakan Berbasis Kasus - Afuan Fajrian Putra; Selfira Salsabilla; Marfuah; Yestias Maharani; Chivalrind Ghanevi Ayuntari (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This service activity aims to improve the competence of accounting teachers in technical skills in the field of taxation. This is because SMK is a vocational education that is ready to provide skilled workers in their fields. In addition, the need for skilled labor in the field of taxation is currently a major need in the industrial world. The material taught in this training is in the form of a tax computer for filling out e-SPT PPh Article 21 and e-Faktur with a case approach. This training was attended by 39 people who are members of the Accounting Subject Teacher Conference (MGMP) throughout Yogyakarta. This activity is carried out for 2 (two) days. The first day is used for providing tax computer training, while the second day is used for exams which function to measure the level of understanding of the training participants. Based on the test results 39 people were declared competent or met certain qualifications so that it is hoped that the understanding and skills that have been obtained in this training can be taught back to students in their respective schools.